(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Surkova L.A. Keywords: the cognition of culture, special courses, journalist, future profession, to state. The article is devoted to special courses on the faculty of philology and journal- istics devoted to the cognition and awareness of culture. The main objective of such courses is to help students to get closer to their future profession. They study to speak and to listen, to state their thoughts and express them in public. Such courses increase the cultural level of prospect journalists.